171k views
5 votes
Solve the equation.
(x-5)(x+3)=0

User Ronginat
by
5.2k points

2 Answers

2 votes
(x-5)(x+3)=0
x^2+3x-5x-15=0
(x^2+3x) (-5x-15)
x(x+3) -5(x+3)
x-5=0 x+3=0
x=5 OR -3
User Annoirq
by
5.6k points
3 votes

Answer:

The solutions to the equation are x=5 x=-3

Explanation:

(x-5)(x+3)=0

Since this is already factored, we can use the zero product property to determine the roots

x-5 =0 x+3 =0

x-5+5= 0+5 x+3-3 = 0-3

x =5 x=-3

The solutions to the equation are x=5 x=-3

User Negin
by
5.5k points